Implementasi Peraturan Presiden Nomor 104 Tahun 2021: Studi Kasus di Desa Plawikan Kecamatan Jogonalan Kabupaten Klaten dalam Bidang Ketahanan Pangan - Clara Jusa Hadel; Rijel Samaloisa (CV. Ulil Albab Corp, 2023)
The implementation of Presidential Regulation Number 104 of 2021 concerning food security in Plawikan Village, Jogonalan District, Klaten Regency itself creates food security by providing stimulants of various vegetable seeds and seeds and chicken livestock to all RTs in Plawikan Village in accordance with Presidential Regulation Number 104 of 2021, which mandates food and animal security programs 20% of the Village Fund. This research uses a qualitative descriptive method. The subjects were the city government and local delegates. The object of study is the City Government's Strategy in expanding food security after the Corona pandemic. Information collection procedures use interview, perception, and documentation strategies. Information investigation procedures through information selection, information presentation, information decline, and purpose. The results showed that (1) the implementation of Presidential Regulation Number 104 of 2021 in Plawikan Village, Jogonalan District, Klaten Regency was carried out through communication, resources, and dispositions or attitudes, and bureaucratic structures. On communication, measures... In resources, the Village Head and his expert staff have expertise in providing relevant information and (2) The constraints faced are the availability of diminishing land resources, due to population pressure and competition for land use between the food sector and the non-food sector. Specifically, the problems associated with food security are the following